The Contribution of Culture and Ethnicities in Leading the Organizational Change at the Indonesia’s Region - Wustari L Mangundjaya (Siber Nusantara Review, 2025)
Today the organization is boundaryless, and every employee has to be ready to be placed anywhere, the place that is new and different from their original location. As a result, understanding other cultures s well as the ability to live and adapt in various business and culture is one of the skills that needs to be possessed. Meanwhile, to face the VUCA condition, every organization needs to change and adapt to the environment. This condition requires a competent change leader that understands the culture. This study aims to check the perceived roles of change leaders in each subculture in Indonesia, namely: Acehnese, Javanese, Balinese, and Papuan, to gain insights into the change leader of its role in those regions, by using the qualitative approach by Focused Group Discussion (FGD) and In-Depth Interview (IDI) to collect the data. Participants were emloyees from Aceh (Sumatera), Yogyakarta (Java), Denpasar (Bali), and Merauke (Papua). Content Analysis used to analyse the data based on the categorization. Results from 97 participants showed that the role of Coach was in the first rank, followed by Change Enabler and Change Pioneer. By knowing these results, it is hoped will contribute insights for HR and OD managers who will implement change programs and obtain employees' commitment in various places and cultures.